Sensitive and selective detection of chromium (VI) based on two-dimensional luminescence metal organic framework nanosheets via the mechanism integrating chemical oxidation-reduction and inner filter effect - Qiu, Linjie; Ma, Zhangyan; Li, Peipei; Hu, Xiaojun; Chen, Chao; Zhu, Xiaohua; Liu, Meiling; Zhang, Youyu; Li, Haitao; Yao, Shouzhuo (Journal of hazardous materials, 2021)
Two-dimensional luminescence metal organic framework nanosheets (LMOF) named NH2-CuMOFs were synthesized using Cu (II) nodes coordinated with negatively charged 2-aminoterephthalic acid (NH2-BDC) via a bottom-up strategy, which were first used as the fluorescent probes for the detection of chromium Cr (VI). The nanosheets possess stable fluorescence with the maximum emission wavelength of 436 nm at excitation of 338 nm that can be effectively quenched by hexavalent chromium Cr (VI). The NH2-CuMOFs nanosheets show superior advantage over the linker of NH2-BDC for the excellent selectivity to Cr (Ⅵ) without the interferences of other metal ions. The mechanism investigation suggested that the sensitive detection of Cr (VI) was attributed to the chemical oxidation-reduction (redox) reaction and internal filtration effect (IFE) between Cr (VI) and NH2-CuMOFs nanosheets. Based on this mechanism, the quantitation of Cr (VI) was realized in the linear range of 0.1–20 μM with a detection limit of 18 nM. Moreover, the detection of Cr (VI) in real samples was also conducted with good recovery. This work provides an optical sensing nanoplatform for heavy metal ions based on two-dimensional LMOFs via a novel mechanism integrating chemical redox reaction and IFE, which may promise broad application prospect for two-dimensional luminescence nanosheets. [Display omitted] •2D luminescence metal organic framework (LMOF) nanosheet was synthesized.•NH2-CuMOFs served as a superior sensitive fluorescent nanoplatform for chromium (Ⅵ).•NH2-CuMOFs show excellent selectivity to Cr (Ⅵ) over NH2-BDC.•A new mechanism integrated with redox reaction and internal filtration effect was proposed.•The quantitative of Cr (Ⅵ) based on NH2-CuMOFs nanosheets was realized.